El desarrollo comunitario en la obra de los teóricos más representativos - Moral Vico, Andrés del (Teoría de la Educación. Revista Interuniversitaria, 2009)
Some time has passed since the sistematization and the theory on the Community Development process were begun. Meanwhile, concepts, terms which denote it, points of view, etc. have been modified. At present they have appeared a series of expressions related with as many socieducative interventions which often share common action spaces. This situation becomes more complicate because each one of the interventions uses specific methodologies which come to be added to the wide conceptual spectrum now existent. This reality requires a contextual analysis in order to clarify somewhat the panorama and to obtain and agreement on these which could be considered as Community Development and every term close to it. Between others, a strategy is to study the works of most representatives theorist in this subject. We have divided the different theoretical contributions as it follows: a) Latinoamerican theorists. b) European theorists. c) Spanish theorists.